Quantitative proteomic analysis reveals hub proteins for high temperature-induced male sterility in bread wheat (Triticum aestivum L.) - Liu, Hongzhan; Li, Jinlei; Xie, Liuyong; Wu, Huanhuan; Han, Shuying; Hu, Lizong; Zhang, Fuli; Wang, Hongxing (Frontiers in Plant Science, 2024)
High-temperature (HT) stress can induce male sterility in wheat; however, the underlying mechanisms remain poorly understood. This study examined proteomic alterations across three developmental stages between normal and HT-induced male-sterile (HT-ms) anthers in wheat. Utilizing tandem mass tags-based proteomics, we identified 2532 differentially abundant proteins (DAPs): 27 in the tetrad stage, 157 in the binuclear stage, and 2348 in the trinuclear stage. Analyses through Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathways indicated significant enrichment of these DAPs in seven pathways, namely phenylpropanoid biosynthesis, flavonoid biosynthesis, sphingolipid metabolism, MAPK signaling pathway, starch and sucrose metabolism, response to heat, and response to reactive oxygen species (ROS). Our results indicated the downregulation of DAPs associated with phenylpropanoid biosynthesis and starch and sucrose metabolism, which aligns with anther indehiscence and the lack of starch in HT-ms anthers. By contrast, DAPs in the ROS pathway were upregulated, which aligns with excessive ROS accumulation in HT-ms anthers. Additionally, we conducted protein–protein interaction analysis for the DAPs of these pathways, identifying 15 hub DAPs. The abundance of these hub proteins was confirmed through qRT-PCR, assessing mRNA expression levels of the corresponding transcripts. Collectively, these results offer insights into the molecular mechanisms underlying HT-induced male sterility in wheat at the proteomic level, providing a valuable resource for further research in plant sexual reproduction.